115 W fiber laser with an all solid-structure and a large-mode-area multicore fiber - Ji, Junhua (2020)
We investigate mode-area scaling by means of supermode operation in an all-solid multicore fiber. To obtain a large-mode area (LMA), we designed and fabricated an active double-clad multicore fiber, where each ytterbium-doped core is 19 μm in diameter and has a numerical aperture of 0.067, comparable to the core of the largest available commercial LMA fibers. The six large cores are stacked tightly in a ring structure to enable phase locking of the core fields and supermode operation. The fiber laser performance was investigated in a linear laser cavity with an external Talbot resonator for mode selection. The highest output power achieved was 115 W with an overall 61% slope efficiency corresponding to the pump power. The measured M2 was 1.43 for the central lobe with nearly 70% of the total power.